Neurl4, a novel daughter centriole protein, prevents formation of ectopic microtubule organizing centres - Li, Ji; Korzeniewski, Nina; Duensing, Stefan (EMBO reports, 2012)
Here we identify Neuralized homologue 4 (Neurl4) as a protein that interacts with CP110, a centrosomal protein that regulates centrosome duplication. Neurl4 uses a Neuralized homology repeat to preferentially localize to procentrioles and daughter centrioles. Neurl4 depletion results in ectopic microtubular organizing centres (MTOCs), leading to accumulation of CP110 and recruitment of a cohort of centrosomal proteins. We show that these ectopic MTOCs persist through mitosis and assemble aberrant mitotic spindles. Interestingly, Neurl4 promotes ubiquitylation of CP110, thereby destabilizing this protein. Our results indicate that Neurl4 counteracts accumulation of CP110, thereby maintaining normal centriolar homeostasis and preventing formation of ectopic MTOCs.
Gesehen am 29.10.2018